Merkel cell carcinoma: Overall survival after open biopsy versus wide local excision. (18th July 2015) - Haymerle, Georg; Fochtmann, Alexandra; Kunstfeld, Rainer; Pammer, Johannes; Erovic, Boban M.
ABSTRACT: Background: Merkel cell carcinoma (MCC) is an aggressive neuroendocrine tumor of the skin with a dismal prognosis. Methods: We conducted a retrospective medical chart review of patients with MCC who were initially diagnosed with an open biopsy ( n  = 30) or wide local excision ( n  = 24). Results: Stages I, II, and III disease was found in 38%, 20%, and 16%, respectively. The 2‐year and 5‐year overall and disease‐specific survival rates were 64.8% and 38.8% versus 45.2% and 26.4%, respectively. Cox regression multivariate model, including tissue sampling technique, re‐resection, therapy modalities, pathological staging, and T and N classifications, showed that patients diagnosed initially with an open biopsy have significant worse overall ( p  = .014) and disease‐free ( p  = .005) survival rates compared with patients who had a wide local excision. Conclusion: This study showed an improved overall survival in patients with MCC after wide local excision compared to open biopsy of the primary site at first diagnosis. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1014–E1018, 2016